Aktywność wynalazcza w sektorze technologii związanej z niedosłuchem w konfrontacji z bodźcami popytowymi - Niklewicz-Pijaczyńska, Małgorzata; Sobiecka, Aldona (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The issue of the article focuses on the demand and supply innovation incentives aimed at people with varying degrees of hearing loss. The aim of this publication is to confront actual inventive activity representing the supply side with expectations of their users who create demand-side innovative incentives. Thus, for the purposes of this article will be used two research methods. Inventive activity will be analyzed using the patent metrics tools. Its assessment and identification of users expectations (on the example of hearing aids) will be made based on results of questionnaires
Keywords: patents; innovations; disability; hearing impairment